1996
DOI: 10.1037/0735-7028.27.4.349
|View full text |Cite
|
Sign up to set email alerts
|

Managed care is harmful to outpatient mental health services: A call for accountability.

Abstract: Substantial evidence indicates that managed care is harmful to outpatient mental health services. The thesis is presented that two underlying causes of these harmful effects are (a) inappropriately focusing on cutting outpatient mental health expenses and (b) dramatically reducing outpatient services as a result of managed care economics. Due to the reduced services, it is likely that treatment quality will suffer as well. The probably negative results are as follows: denying services to many who need treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
102
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 66 publications
1
102
2
Order By: Relevance
“…This literature includes numerous empirical surveys of practitioners regarding the impact of managed care on their practices (e.g., Bell, 1999;Murphy, DeBernardo, & Shoemaker, 1998;Phelps, Eisman, & Kohout, 1998;Rothbaum, Bernstein, Haller, Phelps, & Kohout, 1998), most of which have concluded that the impact has been quite negative. In addition, the literature includes nonempirical commentaries on the impact of managed care on psychotherapy (e.g., Karon, 1995;Miller, 1996), most of which describe managed care as having a detrimental effect. However, diagnosis has not been the primary focus of these surveys and commentaries.…”
mentioning
confidence: 99%
“…This literature includes numerous empirical surveys of practitioners regarding the impact of managed care on their practices (e.g., Bell, 1999;Murphy, DeBernardo, & Shoemaker, 1998;Phelps, Eisman, & Kohout, 1998;Rothbaum, Bernstein, Haller, Phelps, & Kohout, 1998), most of which have concluded that the impact has been quite negative. In addition, the literature includes nonempirical commentaries on the impact of managed care on psychotherapy (e.g., Karon, 1995;Miller, 1996), most of which describe managed care as having a detrimental effect. However, diagnosis has not been the primary focus of these surveys and commentaries.…”
mentioning
confidence: 99%
“…Reductions in clinician payment increase profit. These sort of reduced payment levels and carve-outs are exclusive to the mental health payment system and may serve to inhibit access to adequate mental health care by managed care enrollees (Miller, 1996).…”
Section: Money Mental Health and Managed Carementioning
confidence: 99%
“…Fee-for-service insurers, including Medicare, occasionally still offer virtually unlimited mental health care sessions. More often, however, they will cover approximately 20 sessions per year to be used at the discretion of the consumer and the provider (Miller, 1996).…”
Section: Money Mental Health and Managed Carementioning
confidence: 99%
“…[2][3][4][5] Surprisingly few published studies have previously analyzed UM effects on outpatient mental health care. Certainly, there is a substantial body of research on utilization, cost, and sometimes quality effects of broad managed behavioral healthcare approaches such as carve-outs that does not isolate the contributions of specific techniques.…”
Section: Introductionmentioning
confidence: 99%